2015
DOI: 10.1016/j.cortex.2014.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Brain activity during observation and motor imagery of different balance tasks: An fMRI study

Abstract: After immobilization, patients show impaired postural control and increased risk of falling. Therefore, loss of balance control should already be counteracted during immobilization. Previously, studies have demonstrated that both motor imagery (MI) and action observation (AO) can improve motor performance. The current study elaborated how the brain is activated during imagination and observation of different postural tasks to provide recommendations about the conception of non-physical balance training. For th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
167
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(188 citation statements)
references
References 59 publications
18
167
0
3
Order By: Relevance
“…The pattern of MEP modulation with the highest activity during AO + MI of the dynamic task and hardly any activity during passive AO is therefore very similar to the general pattern of brain activity derived from our recent fMRI measures (Taube et al, 2015). In this previous study, we used exactly the same experimental design as in the current study to make direct comparisons possible.…”
Section: Comparison Of Tms and Fmri Datasupporting
confidence: 60%
See 2 more Smart Citations
“…The pattern of MEP modulation with the highest activity during AO + MI of the dynamic task and hardly any activity during passive AO is therefore very similar to the general pattern of brain activity derived from our recent fMRI measures (Taube et al, 2015). In this previous study, we used exactly the same experimental design as in the current study to make direct comparisons possible.…”
Section: Comparison Of Tms and Fmri Datasupporting
confidence: 60%
“…Using another analysis such as small volume correction on a ROI improves the sensitivity and induces a better detection of M1 activity, especially in complex designs with multiple conditions. Using this kind of analysis, Sharma et al (2008) and Taube et al (2015) detected activity in the primary motor cortex during mental simulation. However, although significant activation was detected during AO + MI of balance tasks, no graded activity that depended on the task difficulty or the mental simulation technique (AO + MI, MI, passive AO) could be observed (Taube et al, 2015).…”
Section: Comparison Of Tms and Fmri Datamentioning
confidence: 99%
See 1 more Smart Citation
“…For novices at run 4, this network is localized dorsally, in some of the same regions for novices at the end of the experiment that it appears for engineering students at both time points: in particular, in precuneus and intraparietal sulcus. This may be an indication that novices have begun to engage motor imagery as a means of grasping the concepts of Newtonian force (Calvo-Merino, 2004;Hétu et al, 2013;Kontra et al, 2015;Pilgramm et al, 2016;Schlegel et al, 2013;Taube et al, 2015). However, given their lack of NEURAL REPRESENTATIONS OF ENGINEERING CONCEPTS 35 hands-on experience mapping this concept onto physical engagement, the way the engineering students have done in lab and classroom demonstrations, it is expected that for the novices this mapping would be less veridical and therefore not involve the retrieval of perceptual memories.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that motor imagery alone is more effective than action observation therapy combined with motor imagery for novel motor learning. As evidence of the effectiveness of action observation plus motor imagery, in neuroscience data, Taube et al have shown that greater activation in the mirror neuron system was obtained when subjects observed the movement of others during which time subjects imagined their own body movement in terms of the model's movement [78].…”
Section: Action Observation Therapymentioning
confidence: 99%